2004
DOI: 10.1016/j.jmb.2003.10.058
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanism for Polar Protein Localization in Bacteria

Abstract: We investigate a mechanism for the polar localization of proteins in bacteria. We focus on the MinCD/DivIVA system regulating division site placement in the rod-shaped bacterium Bacillus subtilis. Our model relies on a combination of geometric effects and reaction-diffusion dynamics to direct proteins to both cell poles, where division is then blocked. We discuss similarities and differences with related division models in Escherichia coli and also develop extensions of the model to asymmetric polar protein lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 50 publications
0
35
0
1
Order By: Relevance
“…Modern developments in fluorescence microscopy have led to a new understanding of the organization of bacterial cells, particularly protein and lipid localization (21,56). Analysis of the subcellular localization of diverse proteins and lipids has shown that they are not uniformly distributed.…”
mentioning
confidence: 99%
“…Modern developments in fluorescence microscopy have led to a new understanding of the organization of bacterial cells, particularly protein and lipid localization (21,56). Analysis of the subcellular localization of diverse proteins and lipids has shown that they are not uniformly distributed.…”
mentioning
confidence: 99%
“…Recent findings suggest that DivIVA recognizes the negative curvature of the membrane at the end of the cell as well as at the newly completed septum (Howard 2004;Lenarcic et al 2009;. It is further suggested that DivIVA prefers the greater negative curvature of mature septa over the gentler curvature of the hemispherical poles.…”
Section: Polar Assembliesmentioning
confidence: 99%
“…MipZ in Caulobacter crescentus forms polar gradients to aid division site selection [11]. In Bacillus subtilis, the MinCD complex also forms polar gradients in order to direct division site selection to the mid-plane of the cell [16,17]. In Escherichia coli, the oscillatory dynamics of the Min proteins creates a time-averaged gradient that directs cell division placement [1824].…”
Section: Introductionmentioning
confidence: 99%